Numerical analysis of the melt behavior in a fuel support piece of the BWR by MPS. (April 2017) - Chen, Ronghua; Chen, Lie; Guo, Kailun; Yamaji, Akifumi; Furuya, Masahiro; Tian, Wenxi; Su, G.H.; Qiu, Suizheng
Highlights: The Pb-Bi plate ablation test was successfully analyzed by MPS code. The freezing behavior of molten Fe and Zr in fuel support piece was investigated. Typical melt freezing behavior in fuel support piece was revealed by MPS method. Abstract: The fuel support piece in a boiling water reactor (BWR) is used to brace fuel assemblies. The channel within the fuel support piece is determined to be a potential corium relocation path from the core region to the lower head during the severe accident of BWR. In the present study, the improved ∗∗∗Moving Particle Semi-implicit (MPS) method was adopted to simulate the flow and solidification behavior of the melt in a fuel support piece. The MPS method was first validated against the Pb-Bi plate ablation test that was performed by CRIEPI. The predicted ablation mass of the plate agreed well with the experimental results. Then the flowing and freezing behaviors of molten stainless steel (SS) and zircaloy in the fuel support piece were simulated by MPS method with a three dimensional particle configuration, respectively. In this study, the flow and solidification behavior of SS was simulated first. After all the SS passed through the channel, the flowing behavior of Zr in the fuel support piece was simulated. The simulation results indicated that the crust layer formed on the inner surface of the fuel support piece during the melt discharging process. The fuel support piece was plugged by the solidified zircaloy particles in the lower initial temperature case. The fuel support piece kept intact in all the calculation that were performed under the assumed order of melt injection. The present results could help to reveal the progression of a BWR severe accident.